Prevalence and Factors Associated with Multidrug-Resistant Tuberculosis (MDR-TB) among Presumptive MDR-TB Patients in Tigray Region, Northern Ethiopia - Kibriti Mehari; Tsehaye Asmelash; Haftamu Hailekiros; Tewolde Wubayehu; Hagos Godefay; Tadele Araya; Muthupandian Saravanan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Tuberculosis (TB) is one of the major public health problems. There are alarming reports of increasing multidrug-resistant tuberculosis (MTR-TB) from various parts of the globe, including Ethiopia. This study was designed to determine the prevalence and factors associated with MDR-TB among presumptive MDR-TB cases in Tigray Regional State, Ethiopia. Methods. A cross-sectional study was conducted in Tigray Regional State from 2015 to 2016. Two hundred sputum samples were collected, transported, processed using 2% N-acetyl-L-cysteine-sodium hydroxide, and cultured in LJ medium. Besides, the microscopic examination was performed after ZN staining. Moreover, drug susceptibility test was done using molecular line probe assay. Descriptive statistics and binary and multivariable logistic regression were done. A statistical test was regarded as significant when the P value was <0.05. Results. The prevalence of MDR-TB was found to be 18.5%. About one-fourth (26.5%) of the study participants had sputum smear positive for acid-fast bacilli (AFB). TB culture was positive in 37% of the samples, and rifampicin mono-resistant cases accounted for 3.5% of the presumptive MDR-TB cases. Three (1.5%) were new MDR-TB cases, while the rest had been treated previously for TB. Most (63.5%) of the MDR-TB cases were from 15 to 44 years of age. Age was associated with MDR-TB with a crude odds ratio of 1.06 (CI: 1.02–1.10) and adjusted odds ratio of 1.06 (CI: 1.00–1.11). Conclusions. The prevalence of MDR-TB was found to be high. Preventive measures should be taken to prevent the transmission of MDR-TB in the community.